Dissemination and use of climate information services status in livestock sector in Senegal - Muriithi, Cyrus K; Maina, Wilson Nguru; Siagbe, Golli; Diouf, Latyr; Ouedraogo, Issa (2024)
Livestock is a crucial asset in Senegal, integral to farming systems and the economy, involving 87.1% of farm households and contributing 27.4% to the primary sector GDP and 4.3% to the national GDP. However, the sector faces significant challenges, including climate change, which exacerbates water scarcity, soil degradation, and resource access inequalities. Key issues include limited pasture and feed availability, inadequate water infrastructure, underdeveloped breeding and management practices, and weak marketing systems. These factors reduce livestock productivity and disrupt the value chain, impacting feed, water resources, and the supply of livestock products. Water availability remains a critical constraint, with insufficient and outdated watering facilities causing strain during dry seasons. Pasture limitations are further intensified by low biomass production due to insufficient rainfall and recurrent droughts. Climate change directly affects livestock metabolism, reproductive performance, and health while indirectly reducing feed and water availability. Access to Weather and Climate Information Services (WCIS) is vital for building resilience among farmers and pastoralists. In Senegal, WCIS dissemination has advanced in the crop sector through initiatives by CGIAR programs like CCAFS and AICCRA, in collaboration with ANACIM and government partners. However, livestock advisory services remain underdeveloped in comparison, highlighting the need for comprehensive assessments to address gaps and enhance WCIS for agro-pastoralists and pastoralists.